2007
DOI: 10.1007/s00117-007-1547-z
|View full text |Cite
|
Sign up to set email alerts
|

Kostenüberlegungen zur Ganzkörper-MRT und PET-CT im Rahmen des onkologischen Stagings

Abstract: Whole-body imaging techniques make it possible to reduce the number of necessary separate radiologic examinations and thus time in oncologic staging. A substantial reduction of health care costs seems to be possible in many tumor entities but differences between different tumor entities are decisive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
6

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 37 publications
0
10
0
6
Order By: Relevance
“…Whole-body MR imaging may be an alternative to FDG-PET/CT [43]; it does not require the operator to work with a potentially harmful radiotracer, the safety profile of MR contrast agents is favorable compared with that of iodinated contrast with CT [44], and the costs for a whole-body MR imaging examination (about 575 euros) are approximately two times less than that of a whole-body FDG-PET/CT examination (about 1,123 euros) [45]. In 1998, Eustace et al [46] showed the potential of whole-body MR imaging in primary tumor detection in four patients with CUP, using a short-tau-inversion-recovery sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Whole-body MR imaging may be an alternative to FDG-PET/CT [43]; it does not require the operator to work with a potentially harmful radiotracer, the safety profile of MR contrast agents is favorable compared with that of iodinated contrast with CT [44], and the costs for a whole-body MR imaging examination (about 575 euros) are approximately two times less than that of a whole-body FDG-PET/CT examination (about 1,123 euros) [45]. In 1998, Eustace et al [46] showed the potential of whole-body MR imaging in primary tumor detection in four patients with CUP, using a short-tau-inversion-recovery sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Referring to the costs, Plathow et al 61,. performing a cost-analysis study, demonstrated that both whole-body imaging techniques allow substantial reduction of health care costs in many tumour types.…”
Section: Resultsmentioning
confidence: 99%
“…Dies ist verständlich, da bislang weder Qualitätsan-forderungen noch klare Indikationen definiert wurden. Überlegungen zur Kosteneffizienz sind zudem schwer anzustellen [32]. Bei privater Krankenversicherung kann daher bislang nur der allgemeine Höchstwert für eine MRT angesetzt werden.…”
Section: Kostenüberlegungenunclassified